Chapter 40 The origins and practice of science on British television - Boon, Timothy (Routledge Media and Cultural Studies Companions, 2018)
The Routledge Companion to British Media History provides a comprehensive exploration of how different media have evolved within social, regional and national contexts. The 50 chapters in this volume, written by an outstanding team of internationally respected scholars, bring together current debates and issues within media history in this era of rapid change, and also provide students and researchers with an essential collection of comparable media histories. The Routledge Companion to British Media History provides an essential guide to key ideas, issues, concepts and debates in the field. Chapter 40 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://www.routledgehandbooks.com/doi/10.4324/9781315756202.ch40